Risk of sports-related sudden cardiac death in women. (11th December 2021) - Rajan, Deepthi; Garcia, Rodrigue; Svane, Jesper; Tfelt-Hansen, Jacob
Abstract: Sudden cardiac death (SCD) is a tragic incident accountable for up to 50% of deaths from cardiovascular disease. Sports-related SCD (SrSCD) is a phenomenon which has previously been associated with both competitive and recreational sport activities. SrSCD has been found to occur 5–33-fold less frequently in women than in men, and the sex difference persists despite a rapid increase in female participation in sports. Establishing the reasons behind this difference could pinpoint targets for improved prevention of SrSCD. Therefore, this review summarizes existing knowledge on epidemiology, characteristics, and causes of SrSCD in females, and elaborates on proposed mechanisms behind the sex differences. Although literature concerning the aetiology of SrSCD in females is limited, proposed mechanisms include sex-specific variations in hormones, blood pressure, autonomic tone, and the presentation of acute coronary syndromes. Consequently, these biological differences impact the degree of cardiac hypertrophy, dilation, right ventricular remodelling, myocardial fibrosis, and coronary atherosclerosis, and thereby the occurrence of ventricular arrhythmias in male and female athletes associated with short- and long-term exercise. Finally, cardiac examinations such as electrocardiograms and echocardiography are useful tools allowing easy differentiation between physiological and pathological cardiac adaptations following exercise in women. However, as a significant proportion of SrSCD causes in women are non-structural or unexplained after autopsy, channelopathies may play an important role, encouraging attention to prodromal symptoms and family history. These findings will aid in the identification of females at high risk of SrSCD and development of targeted prevention for female sport participants. Graphical Abstract: